New distribution records and molecular characterization of six commercially important groupers (Teleostei: Perciformes: Epinephelidae) from the Lakshadweep Islands, India - Dhaneesh, K. V.; Kumar, A. Biju; Aneesh, P. T. (Zootaxa, 2026)
This study documents the first recorded occurrence of six commercially important grouper fish species (Teleostei: Perciformes: Epinephelidae) from the Lakshadweep Islands, India. The species documented in this study are the Snubnose grouper Epinephelus macrospilos (Bleeker, 1855), Brownspotted grouper Epinephelus chlorostigma (Valenciennes, 1828), Dotted grouper Epinephelus epistictus (Temminck and Schlegel, 1842), Slender grouper Anyperodon leucogrammicus (Valenciennes, 1828), White-edged lyretail Variola albimarginata Baissac, 1953 and Oblique-banded grouper Epinephelus radiatus (Day, 1868). Both morphological examination and molecular analysis were carried out to characterize and confirm the identity of these species. This investigation represents the first documentation of these six grouper species from the Lakshadweep Islands. The results enhance current understanding of the marine biodiversity of the region and provide valuable information for the management and sustainability of its commercially important fisheries.